Pharmacokinetic variability of anticoagulants in patients with cancer-associated thrombosis: Clinical consequences. (September 2018) - Bellesoeur, Audrey; Thomas-Schoemann, Audrey; Allard, Marie; Smadja, David; Vidal, Michel; Alexandre, Jérôme; Goldwasser, François; Blanchet, Benoît
Abstract: The use of anticoagulants in patients with cancer is challenging as several co-morbidities modifying pharmacokinetic (PK) parameters and significant drug-drug interactions with concomitant anti-neoplastic therapies may lead to PK variability resulting in increased risk of thrombosis or bleeding. Data on the management of patients with cancer-associated thrombosis (CAT) in real life are scarce since patients with cancer presenting with significant comorbidities tend to be excluded from large trials. This review is mostly based on case-reports and pharmacokinetics in an attempt to provide oncologists, with relevant orientation based on our best knowledge to date. Overall, low-molecular-weight heparins (LMWH) are the preferred option for the long-term prophylaxis and treatment of CAT as their benefit-risk was shown superior to vitamin K antagonists (VKA). Direct oral anticoagulants (DOAC) may represent an alternative to LMWH provided that a favorable benefit-risk in patients with CAT is evidenced in the future. We recommend a systematic risk-assessment including body composition, multiple medication, and renal function. Moreover a systematic and early discussion between pharmacist and oncologist should optimize the benefit-risk ratio for each patient.